Cover Feature: Uranium(IV) Thio‐ and Selenoether Complexes: Syntheses, Structures, and Computational Investigation of U−ER2 Interactions (Chem. Eur. J. 1/2022). Issue 1 (15th December 2021) - Gray, Novan A. G.; Price, Jeffrey S.; Emslie, David J. H.
Abstract : Uranium—selenoether linkages have been accessed for the first time, enabling the study of U−SeR2 versus U−SR2 and U−OR2 bonding. The shape of the uranium selenoether complex resembles a butterfly, and the cover art depicts a metamorphosis from the protio‐ligand (caterpillar), to the potassium salt of the ligand (chrysalis), to the uranium complex (butterfly). More information can be found in the Communication by D. J. H. Emslie et al. (DOI: 10.1002/chem.202103580 ). Cover design: N.A.G.G.